Keeping It Alive – Mapping Bangkok’s Diverse Living Culture - Binson, Bussakorn; Komkam, Pattara; Phaosavadi, Pornprapit; Pornprasit, Kumkom (Journal of Urban Culture Research, 2014)
This research project maps Bangkok’s living local culture sites while exploring, compiling and analyzing the relevant data from all 50 districts. This is an overview article of the 2011 qualitative !eld research by the Urban Research Plaza and the Thai Music and Culture Research Unit of Chulalongkorn University to be published in book form under the title Living Local Cultural Sites of Bangkok in 2012. The complete data set will be transformed into a website fortifying Bangkok’s cultural tourism to remedy its reputation as a destination for sex tourism. The !ve areas of cultural activity include the performing arts, rites, sports and recreation, craftsmanship, and the domestic arts. It was discovered that these living local cultural sites mirror the heterogeneity of its residents with their diverse ethnic and cultural backgrounds. There are local culture clusters of Laotians, Khmers, Mon, Chinese, Islam, Brahman-Hinduism, and Sikhs as well as Westerners. It was also found that the respective culture owners are devoted to preserve their multi-generational heritage. The natural beauty of these cultural sites remains clearly evident and vibrant, even though there remain dif!culties hampering their retention. The mapping of these sites are discussed as well as the issues surrounding those cultural sites that are in danger of extinction due to the absence of successors and other supportive factors necessary for their sustainability.